IN SILICO INVESTIGATION OF ECHINODERMATA SECONDARY METABOLITES AS HUMAN IMMUNODEFICIENCY VIRUS TYPE 1 (HIV-1) REVERSE TRANSCRIPTASE INHIBITORS - NAZWIR, NURRAHMA; YANUAR, ARRY; SYAHDI, REZI RIADHI (International Journal of Applied Pharmaceutics, 2020)
Objective: Human immunodeficiency virus (HIV) targets the immune system and weakens immune surveillance and defenses against infections, leading to acute immunodeficiency syndrome. Recent trends in drug discovery from natural sources emphasize investigations of compounds from marine ecosystems. Methods: In this study, we compiled a database of chemical compounds from echinoderms and virtually screened for those that inhibit HIV-1 reverse transcriptase (RT). The database was generated from literature searches. Virtual screening analyses for inhibitors of HIV-1 RT were then performed using AutoDock software. Results: Based on screening results, the top thirteen ranked compounds were nobilisidenol B, Ech_005, 17-deoxyholothurinogenin, 22,25-oxidoholothurinogenin, Ech_022, Ech_026, Ech_021, nobilisidenol A, Ech_025, 5α-cholest-8(14)-ene-3ß,7α-diol, astropecten A, Ech_004, and phrygiasterol. Conclusion: The present in silico screening analyses of compounds from marine ecosystems can be used to identify candidate compounds with high potential as drugs for the treatment of refractory HIV infections.